Who Will Help? Willingness to Work for the Union - Kuruvilla, Sarosh; Fiorito, Jack (Relations industrielles / Industrial Relations, 1994)
This paper proposes and tests a model of a critical union commitment dimension: "Willingness to work" for the union. Organization and social psychological theories, along with previous empirical research, are used to develop the conceptual model, measures, and predictions. These predictions are tested via a two stage regression model, using data from a large sample of Swedish professional union members. As predicted, both attitudinal commitment and subjective norms are critical influences on the individual's willingness to work on behalf of the union.